Impact of Rural-Urban Migration on Income: Case Study of Selected Large & Medium Scale Industries - Anwar, Khalid (Journal of Commerce and Trade, 2007)
It may be said that while the basic cause of migration is low levels of income and lack of job opportunities at the native place, the actual degree of migration is positively related to the expected earnings at the place of migration. The economic compulsion of the work force forces them to migrate outside their villages. Thus viewing the distribution pattern of resources such as land and income among the households in various industries and the villages around the industries one finds that inequality in the income opportunity is a basic cause and effect which influences the migration from one place to another.